A Comparison of Optical Biometers Used in Children for Myopia Control - Mattern, Ann-Isabel; Neller, Kai; Devenijn, Machteld; Schwahn, Hartmut; Langenbucher, Achim; Seitz, Berthold; Kaymak, Hakan (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To assess the reproducibility (i.e., inter-device reliability) of the biometers Topcon MYAH, Oculus Myopia Master, and Haag-Streit Lenstar LS900 with the Carl Zeiss IOLMaster 700 and the intra-subject repeatability in myopic children in order to reliably detect axial growth for myopia management.Methods Twenty-two myopic children (11.1 ± 2.4 yr) with a spherical equivalent of − 3.53 ± 2.35 D were examined with each of the biometers to assess axial length (AL) and corneal parameters (steepK, flatK, meanK, vectors J0, J45), and16 of these children agreed to a second round of measurements. Reproducibility of the first measurements between the IOLMaster and every other biometer was assessed employing a Bland-Altman approach and paired Studentʼs t-test. Repeatability was assessed as intra-subject standard deviation and was used to estimate the minimum time interval required between two AL measurements to reliably detect axial growth of an eye of at least 0.1 mm/year.Results Repeatability for AL measurements was as follows: IOLMaster: 0.05 mm, Myopia Master: 0.06 mm, Myah: 0.06 mm, Lenstar: 0.04 mm; the respective minimal time interval for axial growth assessment in myopia management was estimated as 5.6, 6.6, 6.7, and 5.0 months, respectively. Best reproducibility of the AL measurement was found between IOLMaster and Lenstar [95% Limits of Agreement (LoA) for reproducibility − 0.06 to 0.02]. As regards to the measured means, Lenstar gave measures of AL that were longer than with the IOLMaster by 0.02 mm (p < 0.001). Myopia Master measures of meanK were significantly lower (by 0.21 D with p < 0.001) than the values from the IOLMaster. As for J0, all biometers deviated significantly from IOLMaster measurements (p < 0.05).Conclusion Generally good agreement was observed between all the biometers. When assessing myopia progression in children, a time frame of at least 6 months between the AL measurements is advisable in order to reliably determine any deviation from a normal growth pattern.
Keywords: myopia; axial length; children; biometry; refractive error; progressive myopia